Electrolyte, preparation method thereof and application of electrolyte in zinc ion flow battery
By using rare earth metal salts as electrolyte additives in zinc ionic liquid flow batteries, the crystal orientation of zinc is regulated, and the problems of zinc dendrites and side reactions are solved, and the performance and stability of the battery are improved.
Patent Information
- Application Number
- CN202510907383.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-02
- Publication Date
- 2025-08-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing electrolyte additives are difficult to accurately regulate the crystal orientation of zinc deposition, resulting in the growth and side reactions of zinc dendrites, affecting the performance of zinc ion flow batteries.
Rare earth metal salts are used as electrolyte additives to increase the electrostatic repulsion of specific crystal surfaces by selectively adsorbing on different crystal surfaces on the surface of the zinc negative electrode, thereby inducing zinc to deposition on an orderly (101) crystal surface, inhibiting dendrite growth and hydrogen evolution reaction.
The uniform deposition of zinc is achieved, the Coulombic efficiency and cyclic stability of zinc ion flow batteries are improved, the production cost is reduced, and the electrochemical reversibility is enhanced.
Smart Images

Figure CN120413732A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zinc-bromine flow batteries, and particularly relates to an electrolyte, a preparation method thereof, and an application in a zinc-ion flow battery. Background Art
[0002] With the gradual depletion of environmentally harmful fossil fuels, there has been an obvious trend in the utilization of renewable energy. Grid-level large-scale energy storage technology is the key to improving the utilization efficiency of renewable energy such as solar energy, hydropower, and wind energy, and can reduce carbon emissions on the energy supply side. Store the surplus energy during the peak production period and supply it during the shortage period. It is worth noting that aqueous zinc-bromine flow batteries, with their long cycle life, safety, and high theoretical energy density (440 W h kg -1 ), have become one of the most competitive technologies in distributed large-scale energy storage.
[0003] The development of aqueous zinc-ion flow batteries (ZFBs) aiming at high energy density and long cycle life faces challenges such as zinc anode-related problems, limited voltage window of aqueous electrolytes, and insufficient cathodic electrochemical performance. The most important challenge is the poor reversibility of the zinc anode. In traditional aqueous zinc bromide electrolytes, due to the disordered growth of crystal planes, many discrete zinc protrusions are generated on the zinc anode, and the local electric field at the tip of the dendritic protrusions is enhanced. The strong charge density distribution easily induces dendrite growth and increases the contact area between the anode and the electrolyte, which will promote hydrogen evolution and side reactions, ultimately resulting in low Coulomb efficiency and short battery cycle life. Therefore, uncontrolled zinc dendrite growth and the occurrence of parasitic side reactions are the main reasons for the failure of aqueous zinc-ion flow batteries. In addition, the high working current density exacerbates this problem, further restricting the performance of zinc-bromine flow batteries in high-power density applications. In order to enable Zn to deposit uniformly and smoothly, it is necessary to adjust the growth orientation of specific crystal planes to avoid tip growth.
[0004] Therefore, effective texture control of the zinc anode to exhibit clear crystal orientation orderliness to guide uniform zinc deposition has received increasing attention. Currently, the methods for controlling crystal orientation in ZFBs mainly include: modifying the separator, electrode modification, establishing a protective layer on the negative electrode surface, or using electrolyte additives, etc. Among the above methods, electrolyte additives have become the most commonly used method due to their low cost-effectiveness and ease of use.
[0005] However, the commonly used electrolyte additives at present are all difficult to precisely control the crystal orientation of Zn deposition and inhibit the occurrence of side reactions. At the same time, except for achieving uniform deposition of the (002) Zn crystal plane through preferential exposure, few people pay attention to the mechanism of regulating the uniform deposition behavior of a single crystal plane of Zn by gradually increasing the electrostatic repulsion force of other crystal planes to gradually reduce the growth rate of the crystal plane. There is still a lack of in-depth understanding of the influence mechanism of the crystal texture on the zinc deposition morphology on the zinc metal surface. Therefore, the present invention proposes to use rare earth metal salts as electrolyte additives to construct a new type of Zn anode with high (101) texture. Summary of the Invention
[0006] The purpose of the present invention is to provide an electrolyte, a preparation method thereof, and an application in a zinc-ion flow battery, so as to solve the problem that the existing electrolyte additives in the background technology are difficult to precisely control the crystal orientation of Zn deposition, provide a negative electrode electrolyte that can precisely control the crystal orientation of Zn deposition, fundamentally solve the problems of zinc dendrites and side reactions, and applying it to a zinc-ion flow battery can improve the battery performance.
[0007] To achieve the above purpose, the present invention provides an electrolyte, which uses a supporting electrolyte salt, a zinc salt, and a rare earth element additive as solutes and deionized water as a solvent, and the concentration of the rare earth element additive is 0.1 - 0.5 mo1 / L.
[0008] Preferably, the rare earth element additive is at least one of neodymium sulfate, lanthanum nitrate, lanthanum chloride, cerium nitrate, gadolinium nitrate, and gadolinium chloride.
[0009] Preferably, the supporting electrolyte salt is one of potassium chloride, ammonium chloride, and sodium chloride.
[0010] Preferably, the concentration of the supporting electrolyte salt is 2 - 5 mol / L.
[0011] Preferably, the zinc salt is zinc bromide.
[0012] Preferably, the concentration of the zinc salt is 2 - 5 mol / L.
[0013] The present invention also provides a preparation method for the above-mentioned electrolyte, including the following steps: S1. Take the supporting electrolyte salt and the zinc salt and put them into a beaker. S2. Add deionized water to the beaker and stir to dissolve. S3. Transfer the solution obtained in S2 to a volumetric flask and prepare an electrolyte with the required concentration. S4. Add the rare earth element additive to the electrolyte to obtain the target electrolyte.
[0014] The present invention also provides an application of the above electrolyte in a zinc-ion flow battery.
[0015] Therefore, an electrolyte provided by the present invention, a preparation method thereof, and an application in a zinc-ion flow battery have the following beneficial effects: (1) After adding a rare earth element additive to the electrolyte, the rare earth metal cations in the rare earth element additive have selective adsorption on different crystal planes on the surface of the zinc negative electrode, so that the orientation of zinc on the fixed crystal plane is high, and zinc is deposited orderly on the fixed crystal plane, thus fundamentally solving the problem of zinc dendrites. Specifically, due to the greater adsorption energy and more adsorption quantity of rare earth metal cations on the (002) plane and the (100) plane, the rare earth metal cations will preferentially adsorb on the (002) and (100) crystal planes of the Zn coating on the carbon felt, and by continuously increasing the electrostatic repulsion force on the (002) and (100) crystal planes, the Zn 2+ ions are forced to deposit on the (101) crystal plane, gradually reducing the growth kinetics of the (002) plane and the (100) plane, thereby inducing the preferential growth of the (101) plane to form a flat and dense deposition layer, thus realizing dendrite-free zinc deposition. In addition, in the repeated galvanizing / stripping cycles, the adsorption layer formed by inert rare earth metal cations will not be consumed, and even at a high working current, it has a high degree of orientation, thereby inducing the orderly deposition of zinc on the carbon fiber on the (101) crystal plane, effectively inhibiting hydrogen evolution and tip effects.
[0016] (2) By using rare earth metals with potential-preferred zinc reduction and high hydrogen evolution overpotential, the hydrogen evolution overpotential of zinc on the current collector can be increased, the occurrence of hydrogen evolution side reactions is inhibited, and when it is applied to a zinc-ion flow battery, excellent Coulomb efficiency and long-term cycle stability of the battery are realized, providing a new way for enhancing the electrochemical reversibility of MZAs textures.
[0017] (3) This method does not require additional processes, reduces production costs, and improves production efficiency.
[0018] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Description of the Drawings
[0019] Figure 1Adsorption quantities and adsorption energies of zinc ions and gadolinium ions on different zinc crystal planes in the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention with and without gadolinium nitrate; wherein, a is the Helmholtz plane structure configuration in the interfacial layer of the (002)Zn crystal plane obtained by MD simulation; b is the Helmholtz plane structure configuration in the interfacial layer of the (100)Zn crystal plane obtained by MD simulation; c is the Helmholtz plane structure configuration in the interfacial layer of the (101)Zn crystal plane obtained by MD simulation; d is the adsorption quantities of different cations in the interfacial layers of the (002), (100) and (101)Zn crystal planes; e is the adsorption energy of gadolinium ions on the (002), (100) and (101)Zn crystal planes. Figure 2 XRD patterns of zinc deposition on carbon felt in the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention with and without gadolinium nitrate, at a current density of 20 mA cm -2 , comparison of zinc crystal plane orientations at different deposition times; wherein, a is the XRD pattern of the growth behavior of zinc on carbon felt in the electrolyte without gadolinium nitrate prepared in Comparative Example 1; b is the XRD pattern of the growth behavior of zinc on carbon felt in the electrolyte with gadolinium nitrate prepared in Example 1. Figure 3 Morphology diagrams of zinc deposition on three-dimensional carbon felt in the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention with and without gadolinium nitrate, at a current density of 20 mA cm -2 , comparison of zinc deposition morphologies at different deposition times; wherein, a is the zinc deposition morphology in the electrolyte without gadolinium nitrate prepared in Comparative Example 1; b is the zinc deposition morphology in the electrolyte with gadolinium nitrate prepared in Example 1. Figure 4 Morphology diagrams of zinc deposition on carbon paper in the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention with and without gadolinium nitrate, at a current density of 20 mA cm -2 , comparison of zinc deposition morphologies at different deposition times; wherein, a is the zinc deposition morphology in the electrolyte without gadolinium nitrate prepared in Comparative Example 1; b is the zinc deposition morphology in the electrolyte with gadolinium nitrate prepared in Example 1. Figure 5 Research on hydrogen evolution in the electrolytes prepared in Example 1 and Comparative Example 1 of the present invention with and without gadolinium nitrate; wherein, a is the LSV curve of the electrolyte with and without gadolinium nitrate; b is the Tafel curve of the electrolyte with and without gadolinium nitrate; c is at a current density of 50 mA cm -2 , areal capacity of 5 mAh cm -2 , XRD pattern of deposited Zn after 50 cycles of the Zn||Zn symmetric flow battery using the electrolyte with and without gadolinium nitrate; d is at a current density of 40 mAcm -2 , areal capacity of 5 mAh cm-2 Volume change of H₂ during the cycling of a Zn||Zn symmetric flow battery using electrolytes with and without gadolinium nitrate; e is at a current density of 40 mA cm -2 and areal capacity of 5 mAh cm -2 pH change during the cycling of a Zn||Zn symmetric flow battery using electrolytes with and without gadolinium nitrate; Figure 6 For Examples 1 and Comparative Example 1 at room temperature in a Zn||Zn symmetric flow battery, at a current density of 50 mA cm -2 and areal capacity of 5 mAh cm -2 Comparison of charge-discharge performance at ; where a is the cycling performance graph of Comparative Example 1; b is the XRD characterization graph of the negative electrode electrolyte deposit of Comparative Example 1; c is the cycling performance graph of Example 1; d is the XRD characterization graph of the negative electrode electrolyte deposit of Example 1; Figure 7 For Examples 2 and Comparative Example 2 at room temperature in a Zn||Zn symmetric flow battery, at a current density of 100 mAcm -2 and areal capacity of 10 mAh cm -2 Comparison of charge-discharge performance at ; where a is the cycling performance graph of Comparative Example 2; b is the XRD characterization graph of the negative electrode electrolyte deposit of Comparative Example 2; c is the cycling performance graph of Example 2; d is the XRD characterization graph of the negative electrode electrolyte deposit of Example 2; Figure 8 For Examples 3 and Comparative Example 3 in a zinc-bromine flow battery at room temperature, at a current density of 20 mA cm -2 and areal capacity of 10 mAh cm -2 Comparison of charge-discharge performance at ; where a is Comparative Example 3; b is Example 3; Figure 9 For Examples 4 and Comparative Example 4 in a zinc-bromine flow battery at room temperature, at a current density of 40 mA cm -2 and areal capacity of 5 mAh cm -2 Comparison of charge-discharge performance at ; where a is Comparative Example 4; b is Example 4. Detailed implementation methods
[0020] The technical solutions of the present invention will be further described below with reference to the accompanying drawings and embodiments. It should be understood that these embodiments are only used to illustrate the present invention and not to limit the scope of the present invention. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of this application and belong to the protection scope of the present invention.
[0021] As used herein, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with the embodiment can be included in at least one embodiment of the present application. The term "embodiment" appearing in various positions in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or relevance to other embodiments. In principle, in the present application, as long as there is no technical contradiction or conflict, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0022] Unless otherwise defined, the meanings of the technical terms used herein are the same as those commonly understood by those skilled in the technical field to which this application belongs; the use of the relevant terms herein is only for describing specific embodiments and is not intended to limit this application.
[0023] Unless otherwise specified in the present invention, the reagents, instruments, equipment, and performance testing methods used are all the reagents, instruments, equipment, and methods commonly used by those skilled in the art in this field.
[0024] The above technical solutions of the present application will be described in detail below in conjunction with specific embodiments.
[0025] Example 1 This example provides a preparation method for an electrolyte applied to a Zn||Zn symmetric flow battery. This battery is a symmetric battery without distinguishing between positive and negative electrodes, and the electrolyte composition is completely the same. The specific steps are as follows: S1. Weigh zinc bromide and potassium chloride and put them into a beaker.
[0026] S2. Add deionized water to the beaker and stir to dissolve.
[0027] S3. Transfer the solution obtained in S2 to a volumetric flask and prepare an electrolyte with the required concentration.
[0028] S4. Divide the electrolyte obtained in S3 into two equal parts, and add an equal amount of gadolinium nitrate to each of the two parts of the electrolyte to obtain the target electrolyte.
[0029] The prepared electrolyte contains 2 mol / L zinc bromide, 2.5 mol / L potassium chloride, and 0.3 mol / L gadolinium nitrate.
[0030] The electrolyte of this example was used to test in a Zn||Zn symmetric flow battery. The test conditions were: the charge-discharge current density was 50 mA cm -2 , and the areal capacity was 5 mAh cm -2 . The battery was assembled by arranging a positive end plate, a current collector, a graphite plate, a carbon felt, a separator, a carbon felt, a graphite plate, a current collector, and a negative end plate in sequence. The separator was a microporous membrane for commercial zinc-bromine flow batteries, and the effective area of the membrane was 4 cm 2 . After the electrolyte passed through multiple normal charge-discharge cycles in the battery, the battery polarization increased, and the number of cycles > 10600 cycles (2000 hours) (see [[ID=IO]] Figure 6 c), and the cumulative areal capacity was 53 Ah cm -2 . By observing the XRD characterization of the electrolyte and the electrolyte deposit, it was found that there were no by-products in the electrolyte (see Figure 6 d).
[0031] Example 2 This example provides a preparation method for an electrolyte applied to a Zn||Zn symmetric flow battery. The preparation method and the prepared electrolyte are the same as those in Example 1, and will not be repeated here.
[0032] The electrolyte of this example was used to test in a Zn||Zn symmetric flow battery. The test conditions were: the charge-discharge current density was 100 mA cm -2 , and the areal capacity was 10 mAh cm -2 . The battery was assembled by arranging a positive end plate, a current collector, a graphite plate, a carbon felt, a separator, a carbon felt, a graphite plate, a current collector, and a negative end plate in sequence. The separator was a microporous membrane for commercial zinc-bromine flow batteries, and the effective area of the membrane was 4 cm 2 . After the electrolyte passed through multiple normal charge-discharge cycles in the battery, the battery polarization increased, and the number of cycles > 4900 cycles (see Figure 7 c), and the cumulative areal capacity was 49 Ah cm -2 . By observing the XRD characterization of the electrolyte and the electrolyte deposit, it was found that there were no by-products in the electrolyte (see Figure 7 d).
[0033] Example 3 This example provides a preparation method for an electrolyte applied to a zinc-bromine flow battery, which specifically includes the following steps: S1. Weigh zinc bromide and potassium chloride and put them into a beaker.
[0034] S2. Add deionized water to the beaker and stir to dissolve.
[0035] S3. Transfer the solution obtained in S2 to a volumetric flask and prepare an electrolyte solution with the required concentration.
[0036] S4. Divide the electrolyte solution obtained in S3 into two equal parts. Add 1-methyl-1-ethylpyrrolidinium bromide to one part to obtain the positive electrode electrolyte.
[0037] S5. Add gadolinium nitrate to the other part of the electrolyte solution separated in S4 to obtain the negative electrode electrolyte.
[0038] Among them, the prepared positive electrode electrolyte includes 2 mol / L zinc bromide, 2.5 mol / L potassium chloride, and 0.4 mol / L 1-methyl-1-ethylpyrrolidinium bromide (MEP).
[0039] The prepared negative electrode electrolyte includes: 2 mol / L zinc bromide, 2.5 mol / L potassium chloride, and 0.3 mol / L gadolinium nitrate.
[0040] The electrolyte solution prepared in this example is used for testing in a zinc-bromine flow battery. The test conditions are: charge-discharge current density 20 mA / cm -2 , areal capacity 10 mAh / cm -2 , discharge cut-off voltage 0.8V. The stack is a single cell, which is assembled by arranging a positive electrode end plate, current collector, graphite plate, carbon felt, separator, carbon felt, graphite plate, current collector, and negative electrode end plate in sequence. The separator is a microporous membrane for commercial zinc-bromine flow batteries, and the effective area of the membrane is 4 cm 2 . After the electrolyte solution undergoes multiple normal charge-discharge cycles in the battery, the average Coulombic efficiency (CE) of the battery is 98.00%, and the average energy efficiency (EE) of the battery is 76.79%. The number of cycles > 3300 cycles (3300 hours) (see Figure 8 b).
[0041] Example 4 This example provides a preparation method for an electrolyte solution applied to a zinc-bromine flow battery. The preparation method and the prepared electrolyte solution are the same as those in Example 3, and will not be repeated here.
[0042] The electrolyte solution of this example is used for testing in a zinc-bromine flow battery. The test conditions are: charge-discharge current density is 40 mA cm -2 , areal capacity is 5 mAh cm -2 . The battery is assembled by arranging a positive electrode end plate, current collector, graphite plate, carbon felt, separator, carbon felt, graphite plate, current collector, and negative electrode end plate in sequence. The separator is a microporous membrane for commercial zinc-bromine flow batteries, and the effective area of the membrane is 4cm 2After the battery undergoes multiple normal charge-discharge cycles, the average Coulombic efficiency (CE) of the battery is 99.61%, and the average energy efficiency (EE) of the battery is 70.41%. The number of cycles > 2000 (see Figure 9 b).
[0043] Comparative Example 1 This comparative example provides a method for preparing an electrolyte applied to a Zn||Zn symmetric flow battery. The difference from Example 1 is only that no rare earth element additive is added during the preparation of the electrolyte. The prepared electrolyte includes 2 mol / L zinc bromide and 2.5 mol / L potassium chloride.
[0044] The electrolyte of this comparative example is used for testing in a Zn||Zn symmetric flow battery. The test conditions are: the charge-discharge current density is 50 mA cm -2 , and the areal capacity is 5 mAh cm -2 . The battery is assembled by arranging a positive electrode plate, a current collector, a graphite plate, a carbon felt, a separator, a carbon felt, a graphite plate, a current collector, and a negative electrode plate in sequence. The separator is a microporous membrane for a commercial zinc-bromine flow battery, and the effective area of the membrane is 4 cm 2 . After the battery undergoes multiple normal charge-discharge cycles, the battery polarization increases, and the number of cycles < 520 (see Figure 6 a), and the cumulative areal capacity is 2.6 Ah cm -2 . By observing the XRD characterization of the electrolyte and the electrolyte deposit, it is found that there are by-products in the electrolyte (see Figure 6 b).
[0045] Comparative Example 2 This comparative example provides a method for preparing an electrolyte applied to a Zn||Zn symmetric flow battery. The preparation method and the prepared electrolyte are the same as those in Comparative Example 1, and will not be repeated here.
[0046] The electrolyte of this comparative example is used for testing in a Zn||Zn symmetric flow battery. The test conditions are: the charge-discharge current density is 100 mA cm -2 , and the areal capacity is 10 mAh cm -2 . The battery is assembled by arranging a positive electrode plate, a current collector, a graphite plate, a carbon felt, a separator, a carbon felt, a graphite plate, a current collector, and a negative electrode plate in sequence. The separator is a microporous membrane for a commercial zinc-bromine flow battery, and the effective area of the membrane is 4 cm 2 . After the battery undergoes multiple normal charge-discharge cycles, the battery polarization increases, and the number of cycles < 320 (see Figure 7 a), and the cumulative areal capacity is 3.2 Ah cm -2 . By observing the XRD characterization of the electrolyte and the electrolyte deposit, it is found that there are by-products in the electrolyte (see Figure 7 b).
[0047] Comparative Example 3 This comparative example provides a method for preparing an electrolyte for a zinc-bromine flow battery. The only difference from Example 3 is that no rare earth element additive is added when preparing the negative electrode electrolyte. The prepared positive electrode electrolyte includes: 2 mol / L zinc bromide, 2.5 mol / L potassium chloride, and 0.4 mol / L 1-methyl-1-ethylpyrrolidone bromide (MEP); the negative electrode electrolyte includes 2 mol / L zinc bromide and 2.5 mol / L potassium chloride.
[0048] The electrolyte of this comparative example was used in a zinc-bromine flow battery test under the following test conditions: the charge and discharge current density was 20 mA cm -2 , with an areal capacity of 10 mAh cm -2 The battery is assembled in sequence by the positive terminal plate, current collector, graphite plate, carbon felt, diaphragm, carbon felt, graphite plate, current collector, and negative terminal plate. The diaphragm is a commercial zinc-bromine flow battery microporous membrane with an effective area of 4 cm 2 After the battery has been charged and discharged for many times, the average coulombic efficiency (CE) of the battery is 96.27%, the average energy efficiency (EE) of the battery is 76.21%, and the number of cycles is less than 150 (see Figure 8 a).
[0049] Comparative Example 4 This comparative example provides a method for preparing an electrolyte for zinc-bromine flow battery. The preparation method and the obtained electrolyte are the same as those in comparative example 3, and will not be repeated here.
[0050] The electrolyte of this comparative example was used in a zinc-bromine flow battery test under the following test conditions: the charge and discharge current density was 40 mA cm -2 , with an areal capacity of 5 mAh cm -2 The battery is assembled in sequence by the positive terminal plate, current collector, graphite plate, carbon felt, diaphragm, carbon felt, graphite plate, current collector, and negative terminal plate. The diaphragm is a commercial zinc-bromine flow battery microporous membrane with an effective area of 4 cm 2 After the battery has been charged and discharged for many times, the average coulombic efficiency (CE) of the battery is 99.28%, the average energy efficiency (EE) of the battery is 62.35%, and the number of cycles is less than 150 (see Figure 9 a).
[0051] Depend on Figures 1-5 It can be seen that the rare earth metal cations in the rare earth element additives have selective adsorption on different crystal planes on the surface of the zinc negative electrode ( Figure 1 , which makes the orientation of zinc on the fixed crystal plane high ( Figure 2 ), zinc is deposited in an orderly manner with fixed crystal planes ( Figures 3-4), thus fundamentally solving the problem of zinc dendrites, greatly improving the cycle stability of the battery. In addition, this interface can also inhibit the hydrogen evolution side reaction ( Figure 5 ), thus achieving excellent Coulombic efficiency and long-term cycle stability of the zinc-ion flow battery.
[0052] Therefore, the preparation method of the electrolyte provided by the present invention for prolonging the working life of the zinc-bromine flow battery by inhibiting zinc dendrites and side reactions has high economic feasibility, overcomes the problem of poor reversibility of the negative electrode of the existing zinc-halogen flow battery, effectively improves the reversibility of zinc metal, and at the same time inhibits problems such as hydrogen evolution and corrosion at the electrode interface, improves the cycle life and battery performance of the battery, and has great market prospects.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that they can still modify or equivalently replace the technical solutions of the present invention, and these modifications or equivalent replacements cannot make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present invention.
Claims
1. An electrolyte, characterized in that: The electrolyte uses a supported electrolyte salt, a zinc salt, and a rare earth element additive as solutes, and deionized water as a solvent. The concentration of the rare earth element additive is 0.1 - 0.5 mo1 / L.
2. An electrolyte according to claim 1, characterized in that: The rare earth element additive is at least one of neodymium sulfate, lanthanum nitrate, lanthanum chloride, cerium nitrate, gadolinium nitrate, and gadolinium chloride.
3. An electrolyte according to claim 1, characterized in that: The supported electrolyte salt is one of potassium chloride, ammonium chloride, and sodium chloride.
4. An electrolyte according to claim 1, characterized in that: The concentration of the supported electrolyte salt is 2 - 5 mol / L.
5. An electrolyte according to claim 1, characterized in that: The zinc salt is zinc bromide.
6. An electrolyte according to claim 1, characterized in that: The concentration of the zinc salt is 2 - 5 mol / L.
7. The preparation method of an electrolyte according to any one of claims 1-6, characterized in that, It includes the following steps: S1. Take the supported electrolyte salt and the zinc salt and put them into a beaker. S2. Add deionized water to the beaker and stir to dissolve. S3. Transfer the solution obtained in S2 to a volumetric flask and prepare an electrolyte with the required concentration. S4. Add the rare earth element additive to the electrolyte to obtain the target electrolyte.
8. Use of an electrolyte according to any one of claims 1-6, characterized in that: The electrolyte is applied to a zinc ion flow battery.
Citation Information
Patent Citations
Aqueous zinc ion battery electrolyte containing additive, preparation method of aqueous zinc ion battery electrolyte and battery
CN113161631A
Aqueous electrolyte for inhibiting zinc dendrites and zinc ion battery
CN116259860A
Zinc-bromine flow battery electrolyte for inhibiting zinc dendrites and preparation method of zinc-bromine flow battery electrolyte
CN118039991A
Zinc-bromine flow battery electrolyte, preparation method and application thereof
CN119069761A
Secondary battery with autolytic dendrites
US20040202926A1
Cited By
Dendritic crystal-free zinc-bromine flow battery electrolyte, preparation method thereof and zinc-bromine flow battery
CN122291610A